ANALISIS FAKTOR RISIKO STROKE PADA PASIEN RAWAT INAP USIA PRODUKTIF - Fuad, Hayatun; Lestari, Dwi; Rondonuwu, Rolly; Suyati, Suyati (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
Stroke remains one of the world’s leading health problems because it imposes a significant burden in terms of morbidity, disability, and mortality. Stroke is the leading cause of disability and the third leading cause of death after coronary heart disease and cancer. The general objective of this study is to analyze stroke risk factors in hospitalized patients of working age. The study design used in this research is a case-control study. The study was conducted at Dr. Drs. M. Hatta Brain Hospital in Bukittinggi. The study was conducted in April 2025. The study sample consisted of 40 case subjects and 40 control subjects. The sampling technique used was purposive sampling. The research instrument used a research questionnaire. Data analysis was performed using univariate and bivariate methods. The results showed an association between hypertension (p-value: 0.013) and stress (p-value: 0.047). It is recommended that respondents undergo regular health checkups, particularly for blood pressure, and practice effective stress management. Keywords: High Blood Pressure, Stress, Stroke.